A ANALISIS SISTEM PENGAMAN GEDUNG REKTORAT UNIVERSITAS LANCANG KUNING PEKANBARU: Sistem pengaman - abrar tanjung tanjung; zulfahri - - (Jurnal Elektro dan Mesin Terapan, 2020)
The Safety System is one way to overcome the interference of reducing the influence of electric current, such as leakage currents or short circuit due to failure of insulation and natural disasters as well as the result of lightning surges. Lancang Kuning University Rectorate Building is a building that has several rooms that have administrative, academic, financial and lecture activities using electrical equipment. The purpose of this study was to calculate the magnitude of the current per phase, power consumption, power losses and determine the capacity of the safety system and evaluate the grounding system in the Rector Building, Lancang Kuning University. Based on the results of the discussion, the power consumption obtained at the Lancang Kuning University Rectorate Building was 292.95 kW, the balanced current was 50 Amperes, the voltage drop was 5 volts, the power loss at the phase 1 voltage R was 1.54 kW and 3 phase of 2.28 kW, magnitude of power loss in phase 1 S voltage of 0.97 kW and 3 phases of 1.69 kW, power loss at phase T voltage of 1 phase at 1.48 kW kW and 3 phases of 2 , 56 kW, the amount of earth resistance is 59.5 ohms, the safety of the main panel is 80 amperes and the installed load is 38.71 KVA, the maximum load is 315 KVA and the average load is 161.61 kVA.